Leonard Bernstein's Young People's Concerts with the New York Philharmonic - Bernstein, Leonard, 1918-1990.; Englander, Roger; Dubin, Charles; New York Philharmonic; Kultur Video (West Long Branch, NJ : Kultur Video, 2004)
Leonard Bernstein earned glory as a composer, conductor, and pianist (classical and jazz), but nothing gave him more pleasure than the joy of teaching. He presented the unique blend of spoken words and music. He is an intensely interactive teacher, getting his audience to sing, springing a quiz full of trick questions. He can take the most abstruse subject and present them to a young audience with clarity, without condescension, and with a clear sense of the material's value. His subject-matter is enormously varied.
Disc 1. What does music mean? What is American music? What is orchestration? -- Disc 2. What makes music symphonic? What is classical music? Humor in music -- Disc 3. What is a concerto? Who is Gustav Mahler? Folk music in the concert hall -- Disc 4. What is Impressionism? Happy Birthday, Igor Stravinsky. What is Melody? -- Disc 5. The Latin American spirit. Jazz in the concert hall. What is sonata form? -- Disc 6. A tribute to Sibelius. Musical atoms : a study of intervals. The sound of an orchestra -- Disc 7. A birthday tribute to Shostakovich. What is a mode? A toast to Vienna in 3/4 time -- Disc 8. Quiz-concert : how musical are you? Berlioz takes a trip. Two ballet birds -- Disc 9. Fidelio : a celebration of life.
Originally televised between 1958-1972; originally released as a compilation in 1990.
Produced and directed by Roger Englander; some episodes directed by Charles S. Dubin.
New York Philharmonic ; Leonard Bernstein, narrator and conductor.
MPAA rating: Not rated.
DVD, full screen (1.33:1) presentation; soundtracks in Dolby digital 5.1 and Dolby stereo.
Closed-captioned.
Keywords: Music appreciation; Music -- Instruction and study; Music -- Performance; Concerts; Music; Symphonic poems; Folk music; Jazz; Melody; Sonata; Impressionism (Music)